Are patients morally responsible for their errors?. Issue 5 (28th April 2006) - Buetow, S; Elwyn, G
Abstract : Amid neglect of patients' contribution to error has been a failure to ask whether patients are morally responsible for their errors. This paper aims to help answer this question and so define a worthy response to the errors. Recent work on medical errors has emphasised system deficiencies and discouraged finding people to blame. We scrutinise this approach from an incompatibilist, agent causation position and draw on Hart's taxonomy of four senses of moral responsibility: role responsibility; capacity responsibility; causal responsibility; and liability responsibility. Each sense is shown to contribute to an overall theoretical judgment as to whether patients are morally responsible for their errors (and success in avoiding them). Though how to weight the senses is unclear, patients appear to be morally responsible for the avoidable errors they make, contribute to or can influence.